Dilemma in Designing a Mathematics Curriculum: Descriptive Versus Prescriptive Approach - Joshi, Ghan Shyam (Academic Journal of Mathematics Education, 2023)
Developing Nepal’s mathematics curriculum is a challenging task, requiring a crucial decision between prescriptive and descriptive curriculum approaches. This study examines prescriptive and descriptive curriculum approaches, their features, and their importance in developing school-level mathematics curriculum. Conversely, the Nepalese school mathematics curriculum predominantly exhibits a perspective and vertical structure. This study conducts a comprehensive comparative analysis of prescriptive and descriptive curriculum approaches, evaluating their objectives, limitations, and applicability. Based on the available literature, the study suggests that the collaborative curriculum model may be a suitable approach. This model involves the central government in curriculum benchmark design, with state governments defining specific educational goals and actively incorporating local input, ensuring a holistic approach to shaping the school math curriculum. The collaborative model shows promise in effectively addressing contemporary challenges in math teaching and learning issues in school mathematics, ensuring inclusivity and relevance for math learners, and paving the way for a brighter future. Additionally, this study highlights the importance of prioritizing learner identity, fostering ownership of learning, and addressing the unique needs of local communities, states, and the nation. This contributes to greater equity in society and globally.